ANALISA QOS JARINGAN 4G LTE OPERATOR TELKOMSEL DAN XL DI PAINAN - Farras, Raihan; Yuhanef, Afrizal; Pamungkas, Muhammad Putra (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
This report analyzes the Quality of Service (QoS) of 4G LTE networks from Telkomsel and XL operators in Painan, West Sumatra. Along with the rapid advancement of telecommunications technology, improving service quality is a top priority. This research uses drive test method with TEMS Pocket application to measure latency, jitter, packet loss, and throughput parameters. The analysis results show that Telkomsel has a higher throughput, reaching 4362 Kbps, compared to XL's 4013 Kbps. Latency for both operators was measured to be poor, at 1554 ms for Telkomsel which was slightly better than XL with 1677 ms. Jitter also showed similar results, with Telkomsel at 1554 ms and XL at 1677 ms. In addition, packet loss on Telkomsel was recorded at 0.021% and on XL at 0.14%, both of which fall into the excellent category. These findings provide insights for operators to improve network quality and overcome existing problems. Thus, this research contributes to a deeper understanding of 4G network performance in the Painan area and serves as a reference for the development of telecommunications infrastructure in the Painan area, especially Indonesia.